Syntactic flexibility and planning scope: the effect of verb bias on advance planning during sentence recall - van de Velde, Maartje; Meyer, Antje S. (Frontiers in Psychology, 2014)
In sentence production, grammatical advance planning scope depends on contextual factors (e.g., time pressure), linguistic factors (e.g., ease of structural processing), and cognitive factors (e.g., production speed). The present study tests the influence of the availability of multiple syntactic alternatives (i.e., syntactic flexibility) on the scope of advance planning during the recall of Dutch dative phrases. We manipulated syntactic flexibility by using verbs with a strong bias or a weak bias towards one structural alternative in sentence frames accepting both verbs (e.g., strong/weak bias: De ober schotelt/serveert de klant de maaltijd [voor] 'The waiter dishes out/serves the customer the meal'). To assess lexical planning scope, we varied the frequency of the first post-verbal noun (N1, Experiment 1) or the second post-verbal noun (N2, Experiment 2). In each experiment, 36 speakers produced the verb phrases in a Rapid Serial Visual Presentation (RSVP) paradigm. On each trial, they read a sentence presented one word at a time, performed a short distractor task, and then saw a sentence preamble (e.g., De ober…) which they had to complete to form the presented sentence. Onset latencies were compared using linear mixed effects models. N1 frequency did not produce any effects. N2 frequency only affected sentence onsets in the weak verb bias condition and especially in slow speakers. These findings highlight the dependency of planning scope during sentence recall on the grammatical properties of the verb and the frequency of post-verbal nouns. Implications for utterance planning in everyday speech are discussed.